Images of inhabiting at Campo Square in Siena: the integration of Bachelard’s topoanalysis in the interpretation of architectural and urban spaces - Noormohammadi, Susan (Journal of Architecture and Urbanism, 2018)
This paper focuses on the perceptual-psychological experience of place in Campo Square, in the Italian city of Siena. Viewed from this perspective, it contributes to Gaston Bachelard’s topoanalysis and aims to address a phenomenological analysis of the real, and inhabited images embedded in Campo Square. Bachelard focuses on topoanalysis, which is mainly based on the association of all our senses, most importantly the visual, aural, and tactile, with our lived experiences. The main objectives of this paper are to discover, examine, and interpret the real images that are influential in the creation of strong sense of place attachment in Campo Square. Based on qualitative research, including a textual analysis of Gaston Bachelard’s phenomenological imagination, the memorable character of Campo Square will be analyzed. The analysis will then be compared to that of another square, Haidplatz, in Regensburg, Germany. This comparison will reveal links between images of inhabiting (simplicity and protection) and images of our sensory realm in Campo Square and Haidplatz Square. Consequently the findings across the two squares lead the paper to suggest possibilities and solutions in order to propose a framework for the integration of topoanalysis in the interpretation of architectural-urban space. First published online 25 June 2017